2019
DOI: 10.1016/j.mbs.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of dispersal phenomenon in biofilms

Abstract: A mathematical model for dispersal phenomenon in multispecies biofilm based on a continuum approach and mass conservation principles is presented. The formation of dispersed cells is modeled by considering a mass balance for the bulk liquid and the biofilm. Diffusion of these cells within the biofilm and in the bulk liquid is described using a diffusion-reaction equation. Diffusion supposes a random character of mobility. Notably, biofilm growth is modeled by a hyperbolic partial differential equation while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…This is usually justified by the assumption that bacterial cells live suspended in the bulk liquid. Nonetheless, it was recently observed that bacteria tend to organize themselves in biofilm form [27], which are aggregates of cells enclosed in a self-produced matrix [28,29]. Then diffusion phenomena at micro-scale turn out to be of paramount importance for such systems.…”
Section: Fractional Gompertzian-type Models: Previous and New Resultsmentioning
confidence: 99%
“…This is usually justified by the assumption that bacterial cells live suspended in the bulk liquid. Nonetheless, it was recently observed that bacteria tend to organize themselves in biofilm form [27], which are aggregates of cells enclosed in a self-produced matrix [28,29]. Then diffusion phenomena at micro-scale turn out to be of paramount importance for such systems.…”
Section: Fractional Gompertzian-type Models: Previous and New Resultsmentioning
confidence: 99%
“…This draws attention to biofilm dispersal, during which the metabolic activity of the active biofilm cells may be modelled to switch to inactive status (D'Acunto et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…The number of viable cells in multispecies biofilms has been reported to increase gradually during the first 72 h, after which the cell numbers remained constant (Wake et al 2016). This draws attention to biofilm dispersal, during which the metabolic activity of the active biofilm cells may be modelled to switch to inactive status (D'Acunto et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…conversion between active and inactive material), diffusive or other forms of mobility, etc. [15,16,27], as well as the possibility for different material types to move with different velocities [13,25,38]. Upon summing equations (2), we obtain the volume conservation constraint…”
Section: Biofilm Modelmentioning
confidence: 99%
“…From left to right: glucose respiration, glucose to lactate fermentation, and lactate respiration. See(16) for the corresponding flux vectors including stoichiometry.…”
mentioning
confidence: 99%